ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT DALAM MENGGUNAKAN UANG ELEKTRONIK DI KOTA DENPASAR, PROVINSI BALI - Mentari, Adinda Cahaya; M.A.D.E, I. K. G. Bendesa (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No.4, April 2018 (pp. 617-867), 2018)
This research aims to determine relationship between factors that affect interest of using electronic money in  Denpasar City, Bali Province. Electronic money began to be intensified with purpose of improving cashless society toward cost and time efficiency. There are four factors studied in this paper, whiche are factor of price conformity, income, ease of use, and usefullness with each factor has three indicators, so there are totally 12 research variables. The research was conducted with cuantitative method by Confirmatory Factor Analysis (CFA) which test the matching of data with model formed using AMOS 21. The result of this research showed that the model fulfilled the criteria of goodness-of fit by looking at probability value, CMIN / DF, RMSEA, CFI, GFI and RMR. The factor of price conformity with income factor, price conformity factor with factor of ease of use, price conformity factor with usefullness factor, and factor of ease of use with usefullness factor interrelated with significant positive value. Whereas, income factor with factor of ease of use, and income factor with usefullness factor interrelated with positive value but not significant.   Keywords : electronic money, price conformity, income, ease of use, usefullness